Integrasi sistem maklumat geografi (GIS) dan imej pesawat tanpa pemandu (UAV) dalam semakan semula cukai taksiran - Baharom, Syahrulnizam (2013)
Local Authorities are established to provide services to the people under their jurisdiction. The main income of a local authority is through the tax assessment collected each year and is used to return to its responsibilities of providing service, and make development especially infrastructure. However, there is a Local Authority whose income can not cover the expenses of management and thus not able to provide proper services to the people. This situation will result in complaints from residents of the impact of the service provided is not satisfactory. This revenue leakage caused some data not current property holdings that include the holding of property owners who pay less than the proper value. One of the causes of recent data is not the holding of property due to shortage of staff to visit the site to get the latest data. Solution to this problem is to implement the integration of Geographic Information System (GIS) with the image of Unmanned Aircraft Vehicle (UAV) in the management of assessment review. By using this method, the analysis of property-related holdings that have made extension can be done easily and quickly. Based on data holdings with additional property tax value assessment, site visits should not be done in the whole area but just holding property that has been identified only. This method will speed up, saving time, labor and cost compared to using the usual method.